Community Supported Agriculture: to Minimise Farm Level Post-Harvest Losses - Sekar, C. and Raghavan, G.S.V (2007)
The objective of the study is to understand the technical, economic and social issues concerning community supported agriculture (CSA) and to explore the possibilities of implementing the system in India, particularly in Tamil Nadu in line with the community supported agriculture farms of Canada to reduce post-harvest losses. Tamil Nadu, a leading horticultural state, contributes 7.7 per cent to the national horticultural production with 5.7 per cent of the national level area. To meet the daily calorie requirements of 60 million people of Tamil Nadu, about 9,000 tonnes of fruits and vegetables are required while the daily availability is nearly 2,600 tonnes. This indicates that there is a huge gap between demand and supply. The post-harvest losses of fruits and vegetables are to the extent of around 40 per cent. By properly linking the farms with consumers through a community food chain like community supported agriculture, the losses can be controlled besides enriching the nutritional security of various sections of the population. The government and local institutions should come forward to formulate action-oriented programmes and prescribe appropriate policies to initiate community supported agriculture in selected localities on a pilot-basis and make this a demonstration unit, so that its deliverables are made known to everyone.